PENGARUH SISTEM PENGENDALIAN MANAJEMEN PADA INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KESEHATAN OLEH RSUD DR. ISKAK - Angga Febrianto; Elsa Alfa Maharani Yhola; Rifki Firdaus Sukma (Universitas Tulungagung, 2021)
AbstractThe level of community satisfaction is influenced by a management control system that is in synergy with a shared commitment. This study aims to analyze the effect of the management control system on the community satisfaction index on health services by RSUD dr. Iskak. The method used is external secondary data analysis, where the data obtained from the official website of RSUD dr. Iskak is data that is considered reliable as the basis of research. This is in line with the increasingly modern digital era, which must be used to make work easier and add insight. The main point of all this research concludes that all the strategies carried out by the management of RSUD dr. Iskak paid off. The management control system that they have launched is actually implemented in tandem with the commitment of all service providers, which becomes a complete and comprehensive force capable of becoming a strong weapon that climbs the ladder of the organization's vision. This is the main factor for the high community satisfaction index score obtained by RSUD dr. Iskak. AbstractThe level of community satisfaction is influenced by a management control system that is in synergy with a shared commitment. This study aims to analyze the effect of the management control system on the community satisfaction index on health services by RSUD dr. Iskak. The method used is external secondary data analysis, where the data obtained from the official website of RSUD dr. Iskak is data that is considered reliable as the basis of research. This is in line with the increasingly modern digital era, which must be used to make work easier and add insight. The main point of all this research concludes that all the strategies carried out by the management of RSUD dr. Iskak paid off. The management control system that they have launched is actually implemented in tandem with the commitment of all service providers, which becomes a complete and comprehensive force capable of becoming a strong weapon that climbs the ladder of the organization's vision. This is the main factor for the high community satisfaction index score obtained by RSUD dr. Iskak.